Vertical implantable collamer lens as a novel method to increase rotational stability - Lee, Yongwoo; Han, Sang Beom; Auffarth, Gerd U.; Son, Hyeck Soo; Khoramnia, Ramin; Choi, Chul Young; Moon, Kun; An, Sang Il; Lee, Je Myung; Lee, Jong Ho (PLOS ONE, 2024)
Purpose We investigated the vertical implantation of a toric implantable collamer lens (ICL) and compared the rotational stability with that of horizontal implantation. Methods This matched comparative study retrospectively reviewed and analyzed data from patients who underwent ICL implantation from 2003-2022 by 1:1 matching vertical and horizontal (V and H toric groups, respectively) implantation patients according to preoperative astigmatism, spherical equivalent, sulcus-to-sulcus, anterior chamber depth, and ICL size. Visual acuity, manifest refraction, vaulting, and rotation were measured 3 months postoperatively. Results We included 646 eyes (323 each in the V and H toric groups). No statistically significant difference was observed between groups in postoperative visual acuity, refractive error, and astigmatism. Vaulting was lower in the V toric group. (P < 0.001). The mean lens rotation in the V toric group was less than that in the H toric group (1.11 ± 2.84° versus 3.02 ± 10.34°, P = 0.001). The proportion of eyes in the V and H toric groups showing ≥10° of rotation was 2.5% (8 eyes) and 6.5% (21 eyes), respectively (P = 0.014). Despite repositioning from rotation, three (0.9%) and eight (2.5%) eyes required removal owing to lens re-rotation in the V and H toric groups, respectively. Conclusion Toric ICL vertical implantation showed good rotational stability, and appropriate visual acuity correction results with relatively low vaulting. This procedure therefore presents an effective novel method that could replace horizontal toric ICL implantation.
Gesehen am 11.10.2024